How do we know they're getting better? : assessment for 21st-century minds, K-8 - Barell, John (Corwin, 2012)
How do we measure students' inquiry, problem-solving, and critical thinking abilities so that we know they are prepared to meet the challenges of the 21st century? John Barell explains how inquiry leads to problem-solving and provides specific steps for pre, formative and summative assessment that informs instruction of 21st century skills. Included are examples that show how to use today's technology in the classroom and how to use inquiry to develop and assess students' abilities.